Bibliometric analysis of global research trends on regulatory T cells in neurological diseases - Gao, Qian; Li, Xinmin; Li, Yan; Long, Junzi; Pan, Mengyang; Wang, Jing; Yang, Fangjie; Zhang, Yasu (Frontiers in Neurology, 2023)
This bibliometric study aimed to summarize and visualize the current research status, emerging trends and research hotspots of regulatory T (Treg) cells in neurological diseases. Relevant documents were retrieved from the Web of Science Core Collection. Tableau Public, VOSviewer and CiteSpace software were applied to perform bibliometric analysis and network visualization. A total of 2739 documents were included, and research on Treg cells in neurological diseases is still in a prolific period. The documents included in the research were sourced from 85 countries/regions, with the majority of them originating from the United States, and 2811 organizations, with a significant proportion of them coming from Harvard Medical School. Howard E Gendelman was the most prolific author in this research area. Considering the number of documents and citations, impact factors and JCR partitions, Frontiers in Immunology was the most popular journal in this research area. Keywords “multiple sclerosis”, “inflammation”, “regulatory T cells”, “neuroinflammation”, “autoimmunity”, “cytokines” and “immunomodulation” were identified as high frequency keywords. Additionally, “gut microbiota” has recently emerged as a new topic of interest. The study of Treg cells in neurological diseases continues to be a hot topic. Immunomodulation, gut microbiota, and cytokines represent the current research hotspots and frontiers in this field. Treg cell-based immunomodulatory approaches have shown immense potential in the treatment of neurological diseases. Modifying gut microbiota or regulating cytokines to boost the numbers and functions of Treg cells represents a promising therapeutic strategy for neurological diseases.